Evaluation of Candida Albicans Attachment with Two Types of Denture Base (Heat Cured Acrylic & Flexible Resin) Polished By Different Polishing Materials - Areej Sh. Ahmad; Amal A. Rashid; Rafah A. Ibrahim (University of Mosul, College of Dentistry, 2014)
Aims: This study aims to measure the effect of three different types of polishing materials (pumice, pumice with soap solution and universal polisher paste) on the surface roughness and the growth of Candida Alicans (C.A) on two types of denture base materials (heat cured acrylic and flexible thermoplastic resin). Materials and Methods: Ninety (90) samples with dimensions (3cm length, 3cm width & 1cm thickness) were prepared & divided into two main groups (45 samples in each) according to the type of base material, heat cured & flexible. Each group was subdivided into three subgroups (15 samples in each) according to the type of polishing materials used in this study: Group1: Polished with pumice (control group), Group 2: Polished with (pumice with soap solution), Group 3: Polished with universal polisher paste. Roughness was measured to all samples by Profilometer Tester. After that the samples were incubated in media containing C.A. for 72 hr. at 300 C to count and compare the value of C.A. growth & adhesion.Results: the statistical analysis of roughness test between the heat cured & flexible showed a highly significant differences between samples polished with pumice, t-test=10.594, p<0.01, and significant differences for both groups polished by (pumice + soap solution) & (polishing paste), t-test= 4.651 & 3.173 with p<0.05 respectively. And for both types (Heat cured & Flexible), samples polished with pumice have the lowest number of viable cells count of C.A. (54, 67 respectively) Conclusions: The heat cured acrylic resin samples had a smoother surface than flexible samples. (Pumice) produced smoother surface than (universal polishing paste) and (pumice +soap solution), therefore, C.A. adhesion were higher than samples polished with pumice.